O potencial educativo da linguagem radiofônica - Andrelo, Roseane [UNESP] (My University, 2013)
This study aims at comprehending the dialogic potential of language radiophonic, in context of educational radio stations. This work based on a multidisciplinary approach. The study employed concepts of discourse analysis, mainly media related, dialogism and oral language. One of the conclusions is that language radiophonic has an educational potential, to allow interactivity with the listener. After all, audience participation can happen, even in a limited way, in a direct interaction (phone, email) or on the radio statement, aspect of the construction of language, of particular interest to this work.

Este trabajo busca comprender el potencial dialógico del lenguaje radiofónica, en emisoras educativas. Para eso, se apoya en una abordaje multidisciplinar. Han sido utilizados preceptos de la análisis de discurso; sobretodo de la análisis del discurso de los medios de comunicación; de dialogismo y del lenguaje oral. Una de las conclusiones obtenidas es que el lenguaje radiofónica tiene potencial educativo, que permite la interactividad con la audiencia. Después de todo, la participación de la audiencia puede suceder, incluso de una manera limitada, en una interacción directa (teléfono, correo electrónico) o en el enunciación de la radio, aspecto de la construcción de la lengua, de particular interés para este trabajo.

Este trabalho busca compreender o potencial dialógico da linguagem radiofônica, no contexto de emissoras educativas. Para isso, apoia-se em uma abordagem multidisciplinar. Foram utilizados preceitos da análise de discurso; sobretudo da análise do discurso midiático; de dialogismo e da oralidade. Uma das conclusões extraídas é que a linguagem radiofônica tem potencial educativo, ao permitir a interatividade com o ouvinte. Afinal, participação da audiência pode acontecer, mesmo que de forma limitada, em uma interação direta (telefone, e-mail) ou no próprio enunciado radiofônico, aspecto da construção da linguagem, que interessa particularmente ao presente trabalho.
The educational potential of radio language
El potencial educativo del lenguaje radiofónico
Keywords: Radio; Language radiophonic; Educational radio; Dialogismo; Oral language; Radio; Linguaje radiofônica; Radio educativa; Dialogismo; Linguaje oral; Rádio; Linguagem radiofônica; Rádio educativa; Dialogismo; Oralidade